Kelios pastabos Viduklės šnektos daiktavardžių linksniavimo raidos klausimu - Rosinas, Albertas (Baltistica, 1994)
ON THE DEVELOPMENT OF NOMINAL DECLENSION IN THE VIDUKLĖ SUBDIALECTThe analysis of the differences in the declension systems of the nouns in S. Stanevičius' texts and in the present subdialect of Viduklė allows making the following conclusions:S. Stanevičius’ texts adequately reflect the former declension system of the Viduklė subdialect.At the beginning of the 19th century the Viduklė subdialect contained potential conditions for further morphological changes.3. For almost 200 years the development of the declension system under discussion has been orientated towards unification of certain flexions, i.e. there was a tendency of reducing the number of allomorphs according to a more productive declension model.
Keywords: Viduklės šnekta; daiktavardžių linksniavimas